A simple and robust approach to reducing contact resistance in organic transistors - Zachary A. Lamport (Nature Portfolio, 2018)
Minimizing contact effects in organic semiconductor-based devices is a key step toward the development of a low-cost technology for next-generation electronics. Here, the authors reduce contact resistance in organic devices by engineering electrodes with high work function surface domains.